Bioactive glasses composition and the influence on remineralization and biomineralization - Souza, Marina Trevelin; Benetti, Francine [UNESP]; Angelo Cintra, Luciano Tavares [UNESP]; Zanotto, Edgar Dutra (My University, 2019)
In the range of procedures preconized by the minimal intervention dentistry (MID) practice, enamel and dentine remineralization has been consolidated as an effective strategy to prevent caries and dental erosion. A variety of remineralizing agents have been proposed and tested along the years, but one particular type is drawing significant attention, not only in academia but also commercially, bioactive glasses (BGs). A vast literature has shown that the use of BGs for remineralization, regardless of their formulation or application technique, can be more effective in enamel remineralization than other classical topical agents, such as fluoride and casein phosphopeptide-amorphous calcium phosphate (CPPACP). Bioactive glasses are capable of continuously releasing calcium and phosphate ions into the local environment, leading to the precipitation of a hydroxyl carbonate apatite (HCA) layer, which provides long-term protection for the enamel and dentinal tubules. These features make this biomaterial a very interesting alternative for treating dentine hypersensitivity (DH), and also for remineralization of white spot lesions or after bleaching procedures. Tailoring bioactive glass compositions by incorporating different ions to the original formula has been effective on granting positive outcomes regarding biomineralization. This Chapter presents a concise update on bioactive glasses used for enamel remineralization and the influence of composition changes on their biomineralization potential.
Keywords: Bioactive glasses; Biomineralization; Dental materials; Materials composition; Remineralization